Enhancing mechanical properties of ultrafine-grained tungsten for fusion applications. (February 2023) - Wurmshuber, Michael; Doppermann, Simon; Wurster, Stefan; Jakob, Severin; Balooch, Mehdi; Alfreider, Markus; Schmuck, Klemens; Bodlos, Rishi; Romaner, Lorenz; Hosemann, Peter; Clemens, Helmut; Maier-Kiener, Verena; et al.
Abstract: Tungsten, while showing many favorable properties, faces challenges in high-performance applications due to its brittle nature. One strategy to improve strength and toughness in tungsten is to refine the grain size down to the ultra-fine grained (ufg) regime. However, as the grain size is reduced, the fraction of grain boundaries that provide easy paths for crack growth increases, thereby limiting the gain in ductility. Therefore, strengthening the grain boundaries is of great importance if one wants to tap the full potential of this material. Using ab-initio calculations, potential grain boundary cohesion enhancing doping elements were identified, and doped ultra-fine grained tungsten samples were fabricated from powders and characterized extensively using small-scale testing techniques. We found that additions of boron and hafnium improve the mechanical properties of tungsten remarkably. Furthermore, an additional low-temperature heat treatment of the boron-doped sample promotes grain boundary segregation, enhancing the properties even further. Thus, in this work we provide an effective pathway of improving mechanical properties in ultra-fine grained tungsten using grain boundary segregation engineering. This opens the door for many challenging applications of ufg W in harsh environments. To further underline the potential employment of ufg W in nuclear fusion reactors, a favorable swelling behavior and mechanical property response after irradiation with helium is presented within this work. Highlights: A powder-based fabrication route of ultrafine-grained W utilizing severe plastic deformation is presented. Strength and ductility of ultrafine-grained W are improved by increasing grain boundary cohesion via doping with B and Hf. Annealing leads to hardening-by-annealing effects and increased dopant segregation, improving strength even further. Ultrafine-grained W is resistant to blister formation and pronounced swelling after irradiation with He ions. Helium bubble softening & radiation hardening effects compete and result in a retained hardness after irradiation with He.